The Issue of Observance of National Minorities Rights in the Political Activities of Representatives of the Ukrainians of Bukovyna in 1928-1929. - Піддубний, Ігор (Academia Romana, 2023)
C. Bratianu in 1927 laid the conditions for the change o f power in Romania. The meeting in Alba lulia in May 1928 played an important role in the National Peasant Party coming to power, because the program o f the party's activities for the near fijture was announced there. After the government of I . Maniu came to power in November 1928, the representatives o f the national minorities o f Romania expected changes in the government's attitude towards the observance o f the rights o f national minorities, as well as the political regime liberalisation. The observance of the rights of national minorities for the Ukrainians of Bukovina was seen primarily in the return o f the Ukrainian teaching language to the educational sphere adopted by the government. The resumption of activities was another issue after the abolition of the siege state in northern Bukovina, as well as Ukrainian educational societies, primarily the "Ruska Besida", which performed tasks in educational activities through reading and amateur theatrical groups. The third issue, which should guarantee the implementation o f the first two ones, was to obtain a sufficient number o f seats in parliament for representatives of the Ukrainian community. From mid-October 1928 through February 1929, Ukrainian communities o f Bukovina filed requests for teaching in Ukrainian. The newspaper "Chas" (Time) also dealt with this issue, publishing reports on the meeting o f
Keywords: Bucovina, ukrainians, national minority rights., interwar period